2020
DOI: 10.1038/s41598-020-62354-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential stromal reprogramming in benign and malignant naturally occurring canine mammary tumours identifies disease-modulating stromal components

Abstract: While cancer-associated stroma (CAS) in malignant tumours is well described, stromal changes in benign forms of naturally occurring tumours remain poorly characterized. Spontaneous canine mammary carcinomas (mCA) are viewed as excellent models of human mCA. We have recently reported highly conserved stromal reprogramming between canine and human mCA based on transcriptome analysis of laser-capture-microdissected FFPE specimen. To identify stromal changes between benign and malignant mammary tumours, we have an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…To analyze gene expression changes in COSCC, we specifically isolated tumor cells and matched normal epithelium from clinical FFPE specimens using LCM coupled with RNAseq as previously established [14] , [15] , [16] , [17] . Representative images of tissue specimens and detailed patient characteristics for all cases are shown in Table 1 and Supplementary Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze gene expression changes in COSCC, we specifically isolated tumor cells and matched normal epithelium from clinical FFPE specimens using LCM coupled with RNAseq as previously established [14] , [15] , [16] , [17] . Representative images of tissue specimens and detailed patient characteristics for all cases are shown in Table 1 and Supplementary Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“… [13] ). Hence, our group has established a workflow to isolate specific subpopulations of cells from archival formalin-fixed paraffin-embedded (FFPE) tissue sections by laser-capture microdissection (LCM) followed by RNAseq analysis [14] , [15] , [16] , [17] . Using this approach, we set out to specifically isolate tumor cells and matched normal epithelial cells from 10 cases of COSCC in order to analyze the molecular underpinnings of COSCC and its resemblance with human HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Also important is the realization that similar expression pattern does not necessarily translate to identical biological behaviour across species. While most studies in the field rely on immunohistochemistry and PCR techniques to assess expression of a handful of targets, only recently more sophisticated techniques are starting to be introduced that allow for unbiased cross-species analysis, such as wide-genome characterization of the cancer 178 and RNA-sequencing of subpopulations of stroma and neoplastic cells 14 , 179 . Such unbiased analysis enables to investigate similarities between species and to identify new therapeutic targets.…”
Section: Considerations For the Development Of Targeted Therapies In mentioning
confidence: 99%
“…They revealed strong increases in mesenchymal stem cells, gamma delta T-cells, macrophages, plasmoid dendritic cells, and natural killer T-cells in CAS and demonstrated that commonly deranged pathways between canine and human CAS included angiogenesis, epithelialmesenchymal transition, glycolysis, and immune response pathways. In order to analyze transcriptional reprogramming of adenoma associated stroma (AAS) of 13 canine mammary adenomas compared to previous data from 15 canine mammary carcinomas, Amini et al (95) applied weighted gene coexpression network analysis (WGCNA) and identified six clusters of highly positively correlated genes and subsequently identified four potentially interesting modules including blue, brown, turquoise and yellow modules. They showed that TGFbeta signaling, glycolysis, mitotic spindle, epithelial to mesenchymal transition, mTORC1 signaling, unfolded protein response, apical surface, interferon-gamma response and G2M checkpoint demonstrated greatly increased enrichment only in CAS and pathways involving pancreas beta cells, fatty acid metabolism, spermatogenesis, heme metabolism and IL2-STAT5 signaling showing dramatically reduced enrichment only in CAS.…”
Section: Genetic Heterogeneity and Epigenetics Of Tnbc And Cmtsmentioning
confidence: 99%
“…They also studied the increased expression of Caveolin-1 (Cav1) and FGF2 in CAS. Potential biomarkers for canine and human mammary carcinoma may be EMT-related genes such as COL11A1, COL8A2, and ADAM12 which are overexpressed in mammary carcinoma (95). Matsumoto et al (140) performed immunohistochemical staining of CD4 and CD8 on tissue microarrays of 164 TNBC cases.…”
Section: Biomarkers Tnbc and Cmts (Tumor-associated Biomarkers Cancmentioning
confidence: 99%